TRILOGY ON THE USE OF FOLKLORE IN ELEMENTARY SCHOOLS: LITERACY, CHARACTER EDUCATION, AND SOCIAL CONTROL - Huriyah Padhilah Anasti; Rein De Komar; Alpi Anwar Pulungan; Baiq Annisa Yulfana Nalurita; Titiek Prihatiningsih; Auzi Ilaturahmi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Folktales are a widely used pedagogical instrument in elementary schools. No research has yet integrated the use of folktales into literacy, character education, and social control activities. Such research is urgently needed given the low literacy rate, the critical importance of character education, and the importance of social control in the development of elementary school students. The purpose of this study is to describe how folktales are utilized in elementary schools as a medium for literacy, character education, and social control. This study is a literature review utilizing reading sources in the form of articles published in various journals over the past five years. Based on the research results, it was obtained that various forms of folktales originating from various regions have been utilized in various learning activities. The learning process with the integration of folktales can improve literacy activities, internalization of character education, and social control for elementary school students.